2020
DOI: 10.1016/j.cej.2020.124309
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, simple and sustainable synthesis of ultra-microporous carbons with high performance for CO2 uptake, via microwave heating

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 64 publications
(70 reference statements)
0
26
0
Order By: Relevance
“…For example, incorporation of nitrogen groups into the melamine-based mesoporous carbon structure demonstrated the development of efficient N-doped activated carbons for CO 2 capture and using amino acid ( l -lysine) as a nitrogen precursor can yield N-doped carbon monolith with a high CO 2 capture capacity of 3.1 mmol/g . Apart from the introduction of nitrogen, recent studies have shown strong adsorption potential in porous carbons with narrow micropores (<1 nm), , suggesting that the presence of ultra-micropores is an important factor for improved CO 2 adsorption. However, chemically fusing the porous carbons with amine or nitrogen-containing compounds often results in the drastic reduction of their pore volume and specific surface area due to the pore blocking .…”
Section: Introductionmentioning
confidence: 99%
“…For example, incorporation of nitrogen groups into the melamine-based mesoporous carbon structure demonstrated the development of efficient N-doped activated carbons for CO 2 capture and using amino acid ( l -lysine) as a nitrogen precursor can yield N-doped carbon monolith with a high CO 2 capture capacity of 3.1 mmol/g . Apart from the introduction of nitrogen, recent studies have shown strong adsorption potential in porous carbons with narrow micropores (<1 nm), , suggesting that the presence of ultra-micropores is an important factor for improved CO 2 adsorption. However, chemically fusing the porous carbons with amine or nitrogen-containing compounds often results in the drastic reduction of their pore volume and specific surface area due to the pore blocking .…”
Section: Introductionmentioning
confidence: 99%
“…Microwave‐assisted synthesis was shown to be an excellent method for the preparation of ultramicroporous (ultramicroporosity up to 72%) activated carbons with high CO 2 adsorption capacities and selectivities. [ 110 ] Such ACs with narrow pores, whose activation involved KOH or K 2 CO 3 , exhibited a high CO 2 uptake under 1 bar: up to 5.3 and 4.5 mmol g −1 at 0 °C, and 3.7 and 3.3 at 25 °C, respectively ( Figure ). Moreover, these carbons showed high CO 2 /N 2 selectivity up to 36.…”
Section: Microwave Synthesis Of Nanoporous Materials and Their Applicationsmentioning
confidence: 99%
“…Porous carbons obtained via microwave‐assisted methods with their SSA values and potential applications are summarized in Table 4 . [ 65–122 ]…”
Section: Microwave Synthesis Of Nanoporous Materials and Their Applicationsmentioning
confidence: 99%
“…Under the microwave superheat of graphene, we summarize the forms of 1D nanomaterials, nanoparticles combined with 2D materials, and their synthesis mechanism, which presents a new paradigm for future composite processes and structural optimization of nanocomposites that can be gradually extended for applications in catalysis, [ 33,34 ] sensing, [ 35 ] or energy storage. [ 36,37 ]…”
Section: Microwave‐positioning Assembly Mechanisms and Advantagesmentioning
confidence: 99%
“…As a common material with excellent microwave absorbing properties, the carbon material is widely used in microwave synthesis systems. The absorption of the microwave by carbon materials is conducive to the rapid nucleation and growth of crystals on its surface, [ 16,36,64 ] and the energy enriched on its surface sites can redox some precursors in situ to form composites combined with carbon materials. [ 65–67 ] At the same time, due to the unique physical and chemical properties of carbon materials, they can also build charge transfer channels, accelerate carrier transfer, and increase reaction active sites in the catalytic reaction system.…”
Section: Catalytic Optimization Strategies By Microwavementioning
confidence: 99%